2011
DOI: 10.1097/gme.0b013e3181fcb2a6
|View full text |Cite
|
Sign up to set email alerts
|

Suspected black cohosh hepatotoxicity

Abstract: The results of this meta-analysis of five randomized, double-blind, and controlled clinical trials showed no evidence that iCR has any adverse effect on liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 52 publications
1
20
1
2
Order By: Relevance
“…Remarkable improvement in the liver function after stopping the drug clearly demonstrates that there is a causal relationship. Our evidence may not be as strong as that which is presented by Teschke et al, Firenzouli et al, or Naser et al [3, 10, 12], but we have supporting case reports, such as those found in the paper published by Lim et al, in which black cohosh is described as causing fulminant hepatic failure to the extent that the patient needed transplantation [4]. The essence of this paper is to not discourage the use of black cohosh but to serve as a warning for patients to use it with caution, especially those who are prone to develop liver diseases.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Remarkable improvement in the liver function after stopping the drug clearly demonstrates that there is a causal relationship. Our evidence may not be as strong as that which is presented by Teschke et al, Firenzouli et al, or Naser et al [3, 10, 12], but we have supporting case reports, such as those found in the paper published by Lim et al, in which black cohosh is described as causing fulminant hepatic failure to the extent that the patient needed transplantation [4]. The essence of this paper is to not discourage the use of black cohosh but to serve as a warning for patients to use it with caution, especially those who are prone to develop liver diseases.…”
Section: Discussioncontrasting
confidence: 88%
“…Teschke et al have reported about 69 cases of hepatotoxicity from black cohosh in their paper and say that the evidence of a causal relationship is weak, even nonexistent [10]. Multiple retrospective studies, prospective studies, and meta-analyses done in the past by Teschke et al, Firenzouli et al, and Naser et al claim that they found a lack of evidence demonstrating causality between black cohosh and liver injury [3, 1012]. In their retrospective studies, they all claim either weak or insufficient evidence of black cohosh use causing hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006 EMEA published a warning advising against unrestricted use of Black cohosh (37). Recently a meta-analysis of RCT's on black cohosh showed no evidence of hepatotoxicity (38). Since CAM remedies are not regulated as drugs they can be bought over the counter in pharmacies and convenience stores, without prescription and information about adverse effects, which may lead to a false sense of safety (19).…”
Section: Discussionmentioning
confidence: 99%
“…A rigorous analysis of these cases showed only possible causality, and not probable or certain causality (Mahady et al, 2008;Teschke and Schwarzenboeck, 2009). Also, a meta-analysis of randomized controlled clinical trials for isopropanolic CR extract on 1020 women found no evidence of CR hepatotoxicity (Naser et al, 2011). Isolated cases of reversible complete heart block (McKenzie and Rahman, 2010), muscle damage were also reported (Minciullo et al, 2006), but only temporal relationship and the absence of other identified causal factors were invoked to support these claims.…”
Section: Safetymentioning
confidence: 76%